Internet-delivered mindfulness for people with depression and chronic pain following spinal cord injury: a randomized, controlled feasibility trial - Hearn, Jasmine Heath; Finlay, Katherine Anne (Spinal cord, 2018)
Study design Between-subjects, randomized controlled feasibility study. Objectives Populations with reduced sensory and motor function are at increased risk of depression, anxiety and pain, and may be less geographically mobile. This study explored the efficacy and feasibility of web-based mindfulness training for people with spinal cord injury (SCI). Setting UK community sample. Methods Participants were randomly allocated to an 8-week online mindfulness intervention ( N